Nursing Care in Mild Brain Injury Patients on Intracranial Adaptive Capacity Reduction Diagnosis - Ramadhani, Hanum Rachman; Saputri, Rinda Dwi; Yulanda, Vicentia Nazida; Sari, Fitri Arista; Febrian, Dimas; Kurniawan, Abdul Yohan; Qowi, Nurul Hikmatul; Sandi, Yudisa Diaz Luthfi (Universitas Muhammadiyah Lamongan, 2024)
Introduction: Head injury or Traumatic Brain Injury (TBI) is defined as a disturbance in the normal functioning of the brain that can be caused by a collision, blow, or jolt to the head or a penetrating head injury. Decreased intracranial adaptive capacity is a disturbance of the intracranial dynamics mechanism in compensating for stimuli that can reduce intracranial capacity. This study aims to explore nursing problems in clients with mild brain injury. Methods: This study uses a case report research design. The population in this study were patients admitted to the roudloh room with mild brain injury as many as 4 people. The sample was selected using purposive sampling technique and obtained a sample of 2 patients with a nursing problem of decreased intracranial adaptive capacity. Data collection using surgical medical nursing assessment format. Data was analyzed with descriptive analitic. Results: The assessment results found that both patients experienced headaches, vertigo, nausea and vomiting and blurred vision. The nursing problem raised is a decrease in intracranial adaptive capacity. The intervention given is to provide a 30⁰ head elevation. From the results of the intervention, it was found that the intervention had been resolved. Conclusion: Giving semi fowler position with head elevation 30 ° in patients with nursing problems decreased intracranial adaptive capacity is very effective. The provision of interventions provided for 3 days with a 30 ° head elevation showed that both patients achieved outcome. Keywords: Mild Head Injury, Head Elevation 30⁰, Head Injury